Exploring the correlation between teacher work motivation and engagement in online classes: the mediating role of job satisfaction - Wenqing Wang; Goodarz Shakibaei (BMC Psychology)
Abstract While prior research highlights the impact of teacher work motivation (TWM) on teacher job satisfaction (TJS) and teacher job engagement (TJE), the nuanced relationships among these constructs in the specific context of Iranian teachers in online classes have received limited attention. Addressing this gap, this study examined the interplay between TWM and TJE, with a focus on the mediating role of TJS among Iranian teachers in online classes. To this end, the study adopted a quantitative research design, involving a sample of 412 EFL teachers (female, n = 226, male, n = 186) recruited through convenience sampling. Data were gathered using standardized instruments for measuring TWM, TJS, and TJE, and analyzed using Structural Equation Modeling (SEM). Findings indicated that TWM significantly predicts TJS and TJE. Additionally, the results uncovered that TJS was significantly correlated with TJE. Furthermore, TJS significantly mediated the effect of TWM on TJE. These insights provided tangible implications for various stakeholders, emphasizing the need to prioritize initiatives that cultivate TJS as a pathway to improved engagement and effectiveness.